Dance Extracurricular Activities for Early Childhood Creative Character - Salma Audina Zahrani; Sofa Muthohar; Nilal Muna Fatmawati; Andrew Laurence Yona (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2026)
This study examines the role of extracurricular dance activities in shaping the creative character of early childhood. Dancing not only helps develop gross and fine motor skills but also encourages children’s imagination, innovation, emotional expression, and social skills. Using a qualitative approach, data were collected through observation, interviews, and documentation during the dance learning process. The results of the study show that extracurricular dance activities enable children to freely and individually express diverse dance movements. Children’s creativity is reflected through improvisational movements, and the success of these activities in enhancing creativity also contributes to children’s social and emotional development, including increased confidence. In addition, dance learning strengthens important social and emotional traits such as cooperation, empathy, and self-control. Therefore, this study recommends integrating dance movement activities into the early childhood education curriculum as an effective and enjoyable medium for developing creative character